The Impact of the COVID-19 Lockdown Restrictions on Physical Activity Levels in European Adolescents: A Systematic Review and Meta-Analysis - Tanya O’Brien; Aileen Lynch (European Scientific Journal, ESJ, 2023)
Aim: To evaluate how the COVID-19 public health lockdown restrictions impacted the physical activity levels of European adolescents aged 10-19. Methodology: Databases searched included CINAHL Complete, Medline, APA PsycInfo, AMED, EMBASE, SPORTDiscus, Web of Science, and Cochrane Library. Search terms comprised database-specific synonyms of “Physical Activity” AND “COVID-19” AND “Adolescents”. Included studies compared continuous, quantitative pre-COVID and during-COVID physical activity measurements of healthy adolescents aged 10-19 living in the European Union. The references of relevant systematic reviews were hand-searched for pertinent studies.  Included studies were independently appraised using the Newcastle Ottawa Scale for Cohort Studies followed by meta-analysis. Findings: Database search retrieved 1397 studies, with three further studies discovered through hand searches. After removing duplicates, 898 articles were independently screened in Covidence by two reviewers, resulting in five included studies. Quality Assessment ratings were ‘poor’ (4/5) or ‘fair’ (1/5). Random effects meta-analysis demonstrated a significant decline in European adolescent physical activity levels, with a Standard Mean Difference of 0.44 (95% CI, 0.03, 0.84; P=0.005, 4 studies, n=2286). When analyzed by gender, a non-significant trend of decreased physical activity was found in both boys (0.43, 95% CI, -0.07, 0.93; P=0.09, 3 studies, n=1030) and girls (0.25, 95% CI, -0.33, 0.84; P=0.40, 3 studies, n=1017). Conclusion: Though overall study quality was poor due to pandemic restrictions, these results indicate that the COVID-19 lockdowns may have significantly negatively impacted already-poor adolescent physical activity levels. This research demonstrates the importance of interventions to encourage physical activity participation in this demographic.